Graphene reinforced resin paint composite material with fluorescence characteristic and preparation method thereof
By doping fluorescent graphene and rare earth complexes in resin paint, the insufficient performance of resin paint composite materials in high corrosion or high strength environments is solved, the self-detection and safety of the material are improved, and the life of the coating is extended.
Patent Information
- Application Number
- CN202510075340.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
AI Technical Summary
Existing resin paint composite materials have limited enhancement performance in high corrosion or high strength environments, short coating life, and difficult to achieve real-time status monitoring, which cannot meet the needs of certain special application scenarios.
By doping fluorescent graphene into the resin paint, the interface bond between graphene and resin is enhanced, and the advantages of fluorescence display of resin paint are given, and the luminous performance of rare earth complexes can be used to achieve self-detection and safety improvement of the material.
It realizes the excellent luminous characteristics of resin paint composite materials, enhances the physical properties of the material, has the functions of real-time status monitoring and safety warning, and extends the service life of the coating.
Smart Images

Figure CN119842321A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite material technology, and in particular to a graphene-enhanced resin paint composite material with fluorescent properties and a preparation method thereof. Background Art
[0002] Graphene is a two-dimensional nanomaterial composed of a single layer of carbon atoms arranged in a hexagonal honeycomb structure. It has attracted much attention in the field of composite materials due to its excellent mechanical properties, electrical conductivity and thermal conductivity. The enhanced function of graphene mainly depends on its interfacial bonding with the matrix material (such as resin). However, due to its strong hydrophobicity and non-polar surface, graphene itself is difficult to form a good interfacial bonding with most matrix materials, which greatly restricts its application in composite materials.
[0003] Resin paint is a kind of coating widely used in industry, construction and bonding fields. Due to its excellent film-forming property, adhesion and corrosion resistance, it has become an ideal substrate for anti-corrosion coatings and primers. However, existing resin paint composite materials show limited enhancement performance and short coating life in high-corrosion or high-strength environments. At the same time, traditional resin paints are difficult to achieve real-time status monitoring and cannot meet the needs of certain special application scenarios. Therefore, in addition to high requirements for the mechanical properties and corrosion resistance of the material, people also hope that the resin paint material has fluorescent properties so that the service life of the material or the integrity of the coating can be monitored through changes in fluorescence intensity to achieve self-detection; and provide visible warning effects at night or in low-light environments to improve safety. Rare earth metals have excellent fluorescence emission properties due to their special electronic structure and have become the main research direction of fluorescent materials. Rare earth complexes can further adjust the luminescence properties by combining with organic ligands, but their poor dispersibility limits their application in composite materials.
[0004] Therefore, in order to improve the interfacial compatibility, graphene usually needs to be modified so that it can better combine with the resin matrix. In addition, the fluorescence properties of graphene have also attracted a lot of research interest. Introducing fluorescent graphene into resin paint is expected to solve the technical bottlenecks of enhancing performance and fluorescence function at the same time.
[0005] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a graphene-enhanced resin paint composite material with fluorescent properties, in which fluorescent graphene is doped into the resin paint to enhance the interface between the graphene filler and the resin, while giving the resin the advantage of fluorescent display. It has excellent luminescent properties and can be widely used in anti-corrosion coatings, concrete primers, industrial floor paints, adhesives, etc.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A graphene-enhanced resin paint composite material with fluorescent properties, the composite material comprising resin paint, fluorescent graphene, a curing agent and a diluent;
[0009] Calculated by mass percentage, the amount of fluorescent graphene added is 0.1% to 2.5% of the mass of the resin paint; the amount of curing agent added is 20% to 30% of the mixed mass of fluorescent graphene and resin paint; the amount of diluent added is 5% to 10% of the mixed mass of fluorescent graphene and resin paint;
[0010] Fluorescent graphene is prepared by reacting graphene oxide, rare earth nitrate and organic ligand in a water bath.
[0011] Among them, the antenna effect transfers energy to the rare earth ion because the ligand has a large UV absorption capacity. The ligand plays the role of a sensitizer. Resonance controls the energy transfer efficiency, which is related to the 4f electron exchange between the rare earth ion and the ligand triplet π electron system. On the one hand, by enhancing the rigid structure and conjugation degree of the ligand; on the other hand, by changing the distance, direction and overlap between the donor and acceptor energy levels. These two aspects can improve the energy transfer efficiency of rare earth complexes and constitute a unique advantage of luminescence.
[0012] After the organic ligand absorbs ultraviolet light, its π electrons transition to the excited state (S1). The ligand molecule transitions from the singlet state (S1) to the triplet state (T1) through intersystem crossing. Since the 4f orbital of the rare earth ion has a good energy match with the triplet energy level of the ligand, efficient energy transfer occurs subsequently. The 4f electrons of the rare earth ion release photons when returning from the excited state to the ground state, which manifests as fluorescence emission. The luminescence of this rare earth organic complex has the advantages of high quantum efficiency, long-life luminescence, adjustable luminescence characteristics, and strong photostability. Therefore, the fluorescence properties of graphene are enhanced under the non-covalent modification of rare earth complexes.
[0013] Preferably, the molar ratio of graphene oxide, rare earth nitrate and organic ligand is 7:1 to 3:3. A higher content of graphene oxide ensures that the rare earth complex can be evenly dispersed on its surface, reduces agglomeration, enhances fluorescence stability, and provides more loading sites for the rare earth complex. The number of ligands is sufficient (1:1 to 3:1 with rare earth ions), can effectively absorb ultraviolet light, and transfer energy to rare earth ions through intersystem crossing. There will not be too many rare earth ions, which will lead to a decrease in energy transfer efficiency, ensuring that the fluorescence emission intensity is maximized.
[0014] Preferably, the graphene oxide is obtained by oxidation of few-layer graphene. Compared with multi-layer graphene, few-layer graphene has a larger specific surface area and more active sites on the surface. The introduction of functional groups such as hydroxyl and carboxyl groups through oxidation improves the dispersibility of graphene oxide in the solution, reduces the agglomeration phenomenon between graphene sheets, makes it easier for rare earth complexes and organic ligands to be loaded on the surface of graphene oxide, and improves the reaction efficiency and the performance of the composite material.
[0015] Preferably, the organic ligand includes any one of isophthalic acid and 1,10-phenanthroline or 1,3,5-benzenetricarboxylic acid and 1,10-phenanthroline.
[0016] 1,10-Phenanthroline is a nitrogen-containing heterocyclic ligand. Isophthalic acid or 1,3,5-benzenetricarboxylic acid is used as a carboxylic acid ligand. The two work synergistically. 1,10-Phenanthroline provides nitrogen coordination sites to form a stable chelate ring with rare earth ions. The carboxylic acid ligand coordinates with the rare earth ions through the carboxyl group, giving the complex a multi-dentate coordination structure, further improving the coordination stability of the rare earth complex, ensuring that the rare earth complex is not easily decomposed under harsh conditions such as light and high temperature, thereby maintaining good fluorescence properties.
[0017] In the present invention, the combination of different ligands (such as 1,10-phenanthroline and carboxylic acid ligands) can regulate the local coordination environment of rare earth ions, thereby adjusting the color and purity of fluorescence emission. The different molecular symmetries of isophthalic acid and 1,3,5-benzenetricarboxylic acid can provide different coordination geometries for rare earth complexes, further improving the luminescence performance.
[0018] Preferably, the molar ratio of isophthalic acid to 1,10-phenanthroline is 4.5:3. A higher ratio of isophthalic acid (carboxylic acid ligand) provides multi-dentate coordination ability, and rare earth ions can combine with multiple carboxyl groups to form stable multi-nuclear or multi-dentate complexes. The nitrogen coordination of 1,10-phenanthroline provides auxiliary stabilization, thereby enhancing the overall structural stability of the complex.
[0019] Preferably, the molar ratio of 1,3,5-benzenetricarboxylic acid to 1,10-phenanthroline is 1:1. Due to the tricarboxyl symmetrical structure of 1,3,5-benzenetricarboxylic acid, its 1:1 ratio ensures a more precise coordination geometry with rare earth ions, reduces excessive use of free ligands, and avoids the occurrence of side reactions. At the same time, an equal amount of 1,10-phenanthroline provides an additional π-conjugated electron system for the rare earth complex, thereby optimizing the fluorescence performance.
[0020] Preferably, the rare earth nitrate is a hexahydrate of any one of Sm, Eu, Tb or Dy nitrate. 3+ 、Eu 3+ , Tb 3+ 、Dy 3+ ) has unique 4f electron transition characteristics, Sm 3+ Usually emits orange-red light, Eu 3+ With excellent red light emission characteristics, Tb 3+ Green emission, Dy 3+ It emits yellow light or blue-white light. By selecting different rare earth ions, the fluorescence emission color and performance of the composite material can be flexibly adjusted to meet different application requirements.
[0021] Preferably, the method for preparing fluorescent graphene comprises the following steps:
[0022] S1. Weigh graphene oxide, rare earth nitrate and organic ligand according to molar ratio;
[0023] S2. Fully dissolve the rare earth nitrate in anhydrous ethanol to obtain solution A, and dissolve graphene oxide and organic ligands in another portion of anhydrous ethanol to obtain solution B. Dissolving the rare earth nitrate and organic ligands separately to form separate solutions helps to avoid premature precipitation or local reaction of rare earth ions and ligands before they are evenly mixed. This operation method helps to optimize the experimental process and lays the foundation for obtaining high-quality composite materials.
[0024] S3, solution B is poured into solution A and mixed evenly, rare earth nitrate and organic ligand are dissolved in absolute ethanol respectively, avoiding the interference of ligand and rare earth ion forming complex to the dissolution process, providing a more stable and controllable environment for subsequent reactions, and improving the dissolution efficiency of each component. At the same time, after uniform mixing, the synergy between rare earth ions and graphene oxide can be promoted to form a composite material with better dispersibility and functionality, thereby improving the optical properties of the material. After ultrasound for a period of time, the mixed solution is reacted in a water bath and centrifuged, and the obtained fluorescent graphene is washed to remove the unloaded rare earth complex, and then placed in an oven for drying. In the present invention, before the water bath reaction, the mixed solution is subjected to ultrasonic treatment in order to ensure that graphene can be evenly dispersed in the mixed solution, fully contacted with the rare earth complex, and the smooth occurrence of the water bath reaction is ensured.
[0025] Furthermore, in step S3, the mixed solution is heated in a water bath at a temperature of 60 to 70° C. and stirred for 4 to 6 hours to fully mix the solution. Gentle heating provides sufficient energy for the chemical reaction between the rare earth ions and the ligands, promoting the efficient formation of the rare earth complex. The stirring time of 4 to 6 hours allows the rare earth complex to be gradually and stably generated, avoiding the formation of byproducts or structural instability caused by rapid reactions.
[0026] Furthermore, in step S3, the mixed solution is centrifuged at a rate of 8000 r / min for 3 to 5 times. After the impurities are removed by centrifugation, only the rare earth complex loaded evenly is retained on the surface of the fluorescent graphene, thereby improving the dispersibility and reducing the possibility of agglomeration in the solution.
[0027] Furthermore, in step S3, the drying is performed at 80-100° C. for 12-24 hours.
[0028] Preferably, the method for preparing graphene oxide comprises the following steps:
[0029] A1, using a mixed solution of acetone and deionized water to remove organic impurities on the surface of graphene;
[0030] A2, titrating the graphene obtained in step A1 with concentrated nitric acid;
[0031] A3. Wash the graphene surface obtained in step A2 until it is neutral, and dry it to obtain graphene oxide.
[0032] The surface of unmodified graphene is non-polar and chemically inert, while resin is usually a polar material. This polarity difference leads to poor interfacial compatibility between them. Graphene is easy to agglomerate in the resin matrix, resulting in the inability to fully exert the reinforcing effect of graphene on the composite material. Before modification, the acidification process gives graphene a large number of oxygen-containing functional groups, which have strong polarity, making the graphene surface change from non-polar to polar, thereby enhancing the interaction between graphene and the polar resin matrix, especially hydrogen bonding or electrostatic interaction. These functional groups can more easily interact with polar groups (such as amino, hydroxyl, epoxy, etc.) in resin molecules to improve interfacial bonding. The interlayer spacing of graphene is significantly increased relative to unmodified graphene; the mechanical meshing effect of graphene with fluorescent properties and resin after mixing increases, while improving the bonding performance of graphene and resin, thereby extending the service life.
[0033] Furthermore, in step A1, the volume ratio of acetone to deionized water is 2:1, a certain amount of graphene is weighed, and the organic impurities on the surface of the graphene are cleaned with a mixed solution of acetone and deionized water, ultrasonically vibrated for 30 to 60 minutes, and then dried at 80 to 100° C. for 12 to 24 hours. Acetone and deionized water will not chemically react with graphene, and can retain its two-dimensional layered structure while cleaning. Through the combined action of the mixed solution and ultrasound, organic impurities are removed under relatively mild conditions, avoiding damage to the graphene sheet that may be caused by excessively severe chemical treatment.
[0034] Furthermore, in step A2, during titration, the water bath heating temperature is maintained at 78°C, the heating time is 4 to 6 hours, and the concentration of concentrated nitric acid is 65% to 68%. Under the conditions of titration and water bath heating, concentrated nitric acid can effectively oxidize the surface and edge of graphene to generate rich oxygen-containing functional groups. The heating temperature of 78°C and the reaction time of 4 to 6 hours help control the rate of the oxidation reaction, avoid the destruction of the graphene sheet structure caused by severe oxidation, and ensure that the oxidized graphene still retains its two-dimensional layered structure and high specific surface area, thereby showing good mechanical properties and dispersibility in subsequent applications.
[0035] The second purpose of the present invention is to provide a method for preparing a graphene-enhanced resin paint composite material with fluorescent properties, so as to obtain a graphene-enhanced resin paint composite material with fluorescent properties that can be widely used in anti-corrosion coatings, concrete primers, industrial floor paints, adhesives, etc.
[0036] In order to achieve the above object, the technical solution adopted by the present invention is:
[0037] A method for preparing a graphene-enhanced resin paint composite material with fluorescent properties comprises the following steps:
[0038] B1. Evenly mix the fluorescent graphene, resin paint, curing agent and diluent, and mechanically stir in a constant temperature water bath until the graphene with fluorescent properties is evenly mixed in the resin paint to obtain a mixture;
[0039] B2. The mixed material obtained in step B1 is evenly coated on the mold and dried in an oven to accelerate curing.
[0040] Preferably, the added mass percentage of fluorescent graphene in step B1 is 0.1% to 2.5% of the mass of the resin paint, the curing agent in step B1 is polyamide 593, and its mass percentage is 20% to 30% of the mixed mass of fluorescent graphene and resin paint; the diluent is butyl acetate, and its mass percentage is 5% to 10% of the mixed mass of fluorescent graphene and resin paint.
[0041] Fluorescent graphene can provide sufficient fluorescence emission centers within the addition range of 0.1% to 2.5%, ensuring that the material has excellent fluorescence properties and avoiding fluorescence quenching caused by excessive addition; polyamide 593 curing agent is a stable curing agent with good chemical reactivity with the matrix of resin paint, which can significantly improve the curing speed and strength of the coating. The addition of 20% to 30% provides sufficient curing conditions for the mixture of fluorescent graphene and resin paint, so that the coating exhibits excellent durability after curing. Butyl acetate diluent can reduce the viscosity of the mixture, improve the dispersibility of fluorescent graphene and resin paint, and ensure uniform distribution during stirring and coating. The addition of 5% to 10% is sufficient to adjust the viscosity without affecting the curing effect or the final performance of the coating. After butyl acetate evaporates, the coating surface becomes smoother, reducing possible bubbles or coating defects, and improving the appearance quality and fluorescence uniformity of the coating.
[0042] Furthermore, the temperature of the constant temperature water bath in step B1 is at room temperature, which can reduce the viscosity of the system, improve the stirring efficiency, and avoid the damage of the fluorescent graphene structure or fluorescent properties caused by excessively high temperature.
[0043] Furthermore, in step B2, the temperature of the oven is set at 40-60° C., and the curing time is 2-4 hours.
[0044] The beneficial effects of the present invention are:
[0045] The graphene-enhanced resin paint composite material with fluorescence characteristics provided by the present invention is a fluorescent graphene prepared by combining graphene and rare earth complex luminescent materials, and then doped in the resin paint, while giving the resin paint fluorescence characteristics, the physical properties of the resin paint are enhanced, and the rare earth complex is bonded with rare earth luminescent ions using a double ligand (isophthalic acid / 1,10-phenanthroline or 1,3,5-benzenetricarboxylic acid / 1,10-phenanthroline), and then non-covalent functionalization is used to modify graphene, and this method does not require covalent chemical reactions between rare earth complexes and graphene, so complex chemical synthesis steps are avoided, and the excellent properties of rare earth complexes and graphene can be maintained at the same time. This process can not only improve the dispersibility of graphene, but also give the graphene composite material fluorescence characteristics. In addition, the high thermal conductivity of graphene helps to protect the rare earth complex from local thermal damage during decomposition at higher temperatures, thereby further proving that fluorescent graphene has good thermal stability. Fluorescent functionalized graphene improves the interfacial compatibility between graphene and resin, and fluorescent graphene can be more evenly dispersed in resin paint. The preparation method of the present invention is used to prepare a graphene-enhanced resin paint composite material with fluorescent properties. Under ultraviolet light excitation, the resin emits characteristic light, which fully combines the common characteristics of graphene and rare earth complex luminescent materials to further enhance the performance of the resin paint, and opens up innovative application prospects for graphene and resin paint. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0047] Figure 1 This is a picture of the microscopic morphology of the modified graphene in Example 1 of the present invention under a scanning electron microscope;
[0048] Figure 2 This is a picture of the microscopic morphology of graphene with Tb fluorescence characteristics under a scanning electron microscope in Example 1 of the present invention;
[0049] Figure 3 This is a fluorescence emission spectrum of the graphene composite material containing the luminescent central ion Tb with fluorescence characteristics in Example 1 of the present invention, the excitation wavelength is 275nm, and the maximum emission peak is at 542nm; the abscissa is the wavelength, and the ordinate is the intensity;
[0050] Figure 4 TG graph of the rare earth complex prepared in Example 1 of the present invention and the graphene with fluorescent properties. The fluorescent graphene decomposes at a higher temperature, which further proves that the fluorescent graphene has good thermal stability.
[0051] Figure 5 The present invention is a flow chart for preparing a graphene-enhanced resin paint composite material with fluorescent properties. DETAILED DESCRIPTION
[0052] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0054] Components Commercial sources Resin paint Guangzhou Suixin Chemical Co., Ltd. Graphene Graphene Gold Mall Harbin Institute of Technology Graphene Rare earth nitrates Beijing Huawei Ruike Chemical Technology Co., Ltd. 1,10-Phenanthroline Shanghai Zhanyun Chemical Co., Ltd. Polyamide 593 type curing agent Kunshan Jiulimei Electronic Materials Co., Ltd. Butyl acetate Aladdin Biochemical Technology Co., Ltd.
[0055] In addition to the above components, concentrated nitric acid, acetone, 1,3,5-benzenetricarboxylic acid, isophthalic acid and other reagents used in the examples of the present invention were purchased from Aladdin.
[0056] Example 1
[0057] A graphene-enhanced resin paint composite material with fluorescent properties, the composite material comprising resin paint, fluorescent graphene, a curing agent and a diluent; calculated by mass percentage, the added amount of the fluorescent graphene is 1% of the mass of the resin paint; the added amount of the curing agent is 25% of the mixed mass of the fluorescent graphene and the resin paint; the added amount of the diluent is 10% of the mixed mass of the fluorescent graphene and the resin paint;
[0058] Fluorescent graphene is prepared by reacting graphene oxide, rare earth nitrate and organic ligand in a water bath, and the molar ratio of graphene oxide, rare earth nitrate and organic ligand is 7:2:3. Graphene oxide is prepared by oxidation of few-layer graphene, and the organic ligand includes isophthalic acid and 1,10-phenanthroline in a molar ratio of 4.5:3, and the rare earth nitrate is terbium nitrate hexahydrate;
[0059] Furthermore, a method for preparing a graphene-enhanced resin paint composite material having fluorescent properties comprises the following steps:
[0060] Step 1, preparing graphene oxide: weigh a certain amount of graphene, use acetone and deionized water with a volume ratio of 2:1 to remove organic impurities on the surface of the graphene; ultrasonic oscillate for 50 minutes, and then dry at 80°C for 15 hours; titrate the dried graphene with concentrated nitric acid at a concentration of 65%; during the titration, the water bath heating temperature is maintained at 78°C for 5 hours; after the titration is completed, wash the obtained graphene surface to neutrality, and dry at 80°C for 15 hours to obtain Figure 1 Graphene oxide shown;
[0061] Step 2, preparing fluorescent graphene: weighing graphene oxide, terbium nitrate hexahydrate, isophthalic acid and 1,10-phenanthroline in a molar ratio of 7:2:3; fully dissolving terbium nitrate hexahydrate in anhydrous ethanol to obtain solution A, and dissolving graphene oxide, isophthalic acid and 1,10-phenanthroline in another portion of anhydrous ethanol to obtain solution B; pouring solution B into solution A, ultrasonicating for 50 minutes, reacting the mixed solution in a water bath and centrifuging, stirring for 5 hours under the condition of heating the mixed solution in a water bath at a temperature of 65° C., centrifuging the mixed solution at a rate of 8000 r / min, centrifuging 3 times, and then washing the obtained fluorescent graphene to remove unloaded rare earth complexes, and then placing it in an oven and drying it at 80° C. for 15 hours;
[0062] Step 3: Evenly mix the fluorescent graphene, resin paint, polyamide 593 curing agent and butyl acetate, and mechanically stir in a constant temperature water bath until the graphene with fluorescent properties is evenly mixed in the resin paint to obtain a mixture;
[0063] Step 4: Evenly apply the mixture obtained in step 3 to the mold and dry it in an oven at 50°C for 3 hours to accelerate curing.
[0064] The microscopic morphology of the graphene-enhanced resin paint composite material with fluorescent properties under a scanning electron microscope is shown in Figure 2. Figure 2 As shown in the figure, the graphene with fluorescent properties emits bright green light under ultraviolet light; the fluorescence spectrum of the graphene composite material with fluorescent properties is shown in the figure Figure 3 As shown, it is observed that the graphene composite material with fluorescence characteristics has the highest fluorescence intensity when the molar content of rare earth nitrate is 2.0 mMol. Therefore, it can be seen that the graphene composite material with fluorescence characteristics can be used for fluorescence indication of resin paint; Figure 4 Shown are the TG graphs of the prepared rare earth complex and graphene with fluorescent properties. It can be observed that the decomposition rate of the product prepared at around 374°C reaches a peak, indicating that it has good thermal stability and can be used at higher temperatures to obtain products that meet the requirements.
[0065] Example 2
[0066] A graphene-enhanced resin paint composite material with fluorescent properties, the composite material comprising resin paint, fluorescent graphene, a curing agent and a diluent; calculated by mass percentage, the added amount of the fluorescent graphene is 2% of the mass of the resin paint; the added amount of the curing agent is 20% of the mixed mass of the fluorescent graphene and the resin paint; the added amount of the diluent is 5% of the mixed mass of the fluorescent graphene and the resin paint;
[0067] Fluorescent graphene is prepared by graphene oxide, rare earth nitrate and organic ligand in a water bath reaction, and the molar ratio of graphene oxide, rare earth nitrate and organic ligand is 7:3:3. Graphene oxide is prepared by oxidation of few-layer graphene, and the organic ligand includes 1,3,5-benzenetricarboxylic acid and 1,10-phenanthroline in a molar ratio of 1:1, and the rare earth nitrate is europium nitrate hexahydrate;
[0068] Furthermore, a method for preparing a graphene-enhanced resin paint composite material having fluorescent properties comprises the following steps:
[0069] Step 1, preparing graphene oxide: weigh a certain amount of graphene, use acetone and deionized water with a volume ratio of 2:1 to remove organic impurities on the surface of the graphene; ultrasonic oscillate for 50 minutes, and then dry at 80°C for 15 hours; titrate the dried graphene with concentrated nitric acid at a concentration of 65%; during the titration, the water bath heating temperature is maintained at 78°C for 5 hours; after the titration is completed, wash the obtained graphene surface to neutrality, and dry at 80°C for 15 hours to obtain Figure 1 Graphene oxide shown;
[0070] Step 2, preparing fluorescent graphene: weighing graphene oxide, europium nitrate hexahydrate, 1,3,5-benzenetricarboxylic acid and 1,10-phenanthroline in a molar ratio of 7:3:3; fully dissolving europium nitrate hexahydrate in anhydrous ethanol to obtain solution A, and dissolving graphene oxide, 1,3,5-benzenetricarboxylic acid and 1,10-phenanthroline in another portion of anhydrous ethanol to obtain solution B; pouring solution B into solution A, ultrasonicating for 50 minutes, reacting the mixed solution in a water bath and centrifuging, stirring for 5 hours under the condition of heating the mixed solution in a water bath at 65°C, centrifuging the mixed solution at a rate of 8000r / min, centrifuging 3 times, and then washing the obtained fluorescent graphene to remove the unloaded rare earth complex, and then placing it in an oven and drying it at 80°C for 15 hours. The fluorescence spectrum of the complex shows a typical europium (III) red light emission, wherein the main emission peak is at 615nm, which is determined by 5 D0→ 7 The F2 energy level transition is dominant. 1,3,5-Benzenetricarboxylic acid and 1,10-phenanthroline as ligands can transfer the energy of the absorbed ultraviolet light to the europium (III) through the "antenna effect". 5The D0 energy level excites europium ions to emit light, improving their luminous efficiency and presenting a bright red light;
[0071] Step 3: Evenly mix the fluorescent graphene, resin paint, polyamide 593 curing agent and butyl acetate, and mechanically stir in a constant temperature water bath until the graphene with fluorescent properties is evenly mixed in the resin paint to obtain a mixture;
[0072] Step 4: Evenly apply the mixture obtained in step 3 to the mold and dry it in an oven at 50°C for 3 hours to accelerate curing.
[0073] Example 3
[0074] A graphene-enhanced resin paint composite material with fluorescent properties, the composite material comprising resin paint, fluorescent graphene, a curing agent and a diluent; calculated by mass percentage, the added amount of the fluorescent graphene is 2.5% of the mass of the resin paint; the added amount of the curing agent is 30% of the mixed mass of the fluorescent graphene and the resin paint; the added amount of the diluent is 10% of the mixed mass of the fluorescent graphene and the resin paint;
[0075] Fluorescent graphene is prepared by reacting graphene oxide, rare earth nitrate and organic ligand in a water bath, and the molar ratio of graphene oxide, rare earth nitrate and organic ligand is 7:3:3. Graphene oxide is prepared by oxidation of few-layer graphene, and the organic ligand includes isophthalic acid and 1,10-phenanthroline in a molar ratio of 4.5:3, and the rare earth nitrate is samarium nitrate hexahydrate;
[0076] Furthermore, a method for preparing a graphene-enhanced resin paint composite material having fluorescent properties comprises the following steps:
[0077] Step 1, preparing graphene oxide: weigh a certain amount of graphene, use acetone and deionized water with a volume ratio of 2:1 to remove organic impurities on the surface of the graphene; ultrasonic oscillate for 50 minutes, and then dry at 80°C for 15 hours; titrate the dried graphene with concentrated nitric acid at a concentration of 65%; during the titration, the water bath heating temperature is maintained at 78°C for 5 hours; after the titration is completed, wash the obtained graphene surface to neutrality, and dry at 80°C for 15 hours to obtain Figure 1 Graphene oxide shown;
[0078] Step 2, preparing fluorescent graphene: weighing graphene oxide, samarium nitrate hexahydrate, isophthalic acid and 1,10-phenanthroline in a molar ratio of 7:3:3; fully dissolving samarium nitrate hexahydrate in anhydrous ethanol to obtain solution A, dissolving graphene oxide, isophthalic acid and 1,10-phenanthroline in another portion of anhydrous ethanol to obtain solution B; pouring solution B into solution A, ultrasonicating for 50 minutes, reacting the mixed solution in a water bath and centrifuging, stirring the mixed solution in a water bath at a temperature of 65°C for 5 hours, centrifuging the mixed solution at a rate of 8000r / min, centrifuging 3 times, and then washing the obtained fluorescent graphene to remove the unloaded rare earth complex, and then placing it in an oven and drying it at 80°C for 15 hours. The fluorescence spectrum of the complex is mainly orange-red, with a main emission peak at 650nm and a secondary emission peak at 605nm. Isophthalic acid and 1,10-phenanthroline absorb ultraviolet light and transfer energy to Sm 3+ The carboxylic acid group of isophthalic acid provides an effective energy transfer path. The π-π conjugated structure of 1,10-phenanthroline further optimizes the energy level matching, improves the fluorescence intensity, and enhances the fluorescence emission of samarium ions. The electronic environment of the ligand affects the Sm 3+ The local symmetry around enhances the emission from the electric dipole transition, thus highlighting the orange-red main peak;
[0079] Step 3: Evenly mix the fluorescent graphene, resin paint, polyamide 593 curing agent and butyl acetate, and mechanically stir in a constant temperature water bath until the graphene with fluorescent properties is evenly mixed in the resin paint to obtain a mixture;
[0080] Step 4: Evenly apply the mixture obtained in step 3 to the mold and dry it in an oven at 50°C for 3 hours to accelerate curing.
[0081] The above are only preferred embodiments of the present invention, and are not intended to limit the present invention in any form. Although the present invention has been presented as a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A graphene-enhanced resin paint composite material with fluorescent properties, characterized in that: The composite material comprises resin paint, fluorescent graphene, a curing agent and a diluent; Calculated by mass percentage, the amount of the fluorescent graphene added is 0.1% to 2.5% of the mass of the resin paint; the amount of the curing agent added is 20% to 30% of the mixed mass of the fluorescent graphene and the resin paint; the amount of the diluent added is 5% to 10% of the mixed mass of the fluorescent graphene and the resin paint; The fluorescent graphene is prepared by reacting graphene oxide, rare earth nitrate and organic ligand in a water bath.
2. The graphene-enhanced resin paint composite material with fluorescent properties according to claim 1, characterized in that: The molar ratio of the graphene oxide, the rare earth nitrate and the organic ligand is 7:1 to 3:
3.
3. The graphene-enhanced resin paint composite material with fluorescent properties according to claim 2, characterized in that: The graphene oxide is prepared by oxidizing few-layer graphene.
4. The graphene-enhanced resin paint composite material with fluorescent properties according to claim 2, characterized in that: The organic ligand includes any one of isophthalic acid and 1,10-phenanthroline, or 1,3,5-benzenetricarboxylic acid and 1,10-phenanthroline.
5. The graphene-enhanced resin paint composite material with fluorescent properties according to claim 4, characterized in that: The molar ratio of isophthalic acid to 1,10-phenanthroline is 4.5:3, and the molar ratio of 1,3,5-benzenetricarboxylic acid to 1,10-phenanthroline is 1:
1.
6. The graphene-enhanced resin paint composite material with fluorescent properties according to claim 2, characterized in that: The rare earth nitrate is a hexahydrate of any one of Sm, Eu, Tb or Dy nitrate.
7. The graphene-enhanced resin paint composite material with fluorescent properties according to claim 1, characterized in that: The preparation method of fluorescent graphene comprises the following steps: S1. Weigh graphene oxide, rare earth nitrate and organic ligand according to molar ratio; S2, fully dissolving the rare earth nitrate in anhydrous ethanol to obtain solution A, and dissolving the graphene oxide and the organic ligand in another portion of anhydrous ethanol to obtain solution B; S3. Pour solution B into solution A and mix evenly. After ultrasonic treatment for a period of time, react the mixture in a water bath and centrifuge it. Then wash the obtained fluorescent graphene to remove the unloaded rare earth complex, and then put it in an oven to dry.
8. The graphene-enhanced resin paint composite material with fluorescent properties according to claim 1, characterized in that: The method for preparing graphene oxide comprises the following steps: A1, using a mixed solution of acetone and deionized water to remove organic impurities on the surface of graphene; A2, titrating the graphene obtained in step A1 with concentrated nitric acid; A3. Wash the graphene surface obtained in step A2 until it is neutral, and dry it to obtain graphene oxide.
9. The method for preparing a graphene-enhanced resin paint composite material with fluorescent properties according to claim 1, characterized in that: The steps are as follows: B1. Evenly mix the fluorescent graphene, resin paint, curing agent and diluent, and mechanically stir in a constant temperature water bath until the graphene with fluorescent properties is evenly mixed in the resin paint to obtain a mixture; B2. The mixed material obtained in step B1 is evenly coated on the mold and dried in an oven to accelerate curing.
10. The method for preparing a graphene-enhanced resin paint composite material with fluorescent properties according to claim 1, characterized in that: The curing agent in step B1 is polyamide 593 type and the diluent is butyl acetate.